Entanglement of Photon-Added Nonlinear Coherent States Via a Beam Splitter. Issue 2 (October 2016) - Honarasa, Gholamreza; Bagheri, Alireza; Gharaati, Abdolrasoul
Abstract : Nonlinear coherent states, photon-added coherent states and photon-added nonlinear coherent states are three of the important generalizations of standard coherent states. In this article, a photon-added nonlinear coherent state and a vacuum state are injected on two input modes of a beam splitter and the entanglement of the output state is investigated using linear entropy as the measure. Then, the impact of nonclassicality of the photon-added nonlinear coherent state on entanglement of the output state is studied.